Apartheid, Growth and Income Distribution in South Africa : Past History and Future Prospects - Corker, Robert; Bayoumi, Tamim (Washington, D.C. : International Monetary Fund, 1991)
Estimates of a supply-side model of the nonprimary sectors, in which particular attention has been paid to modeling key characteristics of the evolution of the apartheid system, are presented. These imply that the wage differential between white and nonwhite workers doing similar jobs fell significantly over the last two decades to around 14 percent in 1990. This relatively small gap implies that medium-term prospects for the advancement of the disadvantaged groups in South Africa depend heavily on their ability to take up skilled employment, with the direct gains from the elimination of apartheid being relatively small.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet